Overcome stereotypes? The discourse on gender violence in three Televisa telenovelas: “Vencer el miedo”, “Vencer el desamor” y “Vencer el pasado” - Gómez Rodríguez, Gabriela (2023)
In 2019, Televisa began the production and transmission of three telenovelas with the central theme of gender violence. The trilogy, Vencer el miedo, Vencer el desamor and Vencer el pasado, intertwines the stories of four protagonists who experience different conflicts associated with the multiple forms of violence they face in their daily relationships with men and women. This article analyzes these telenovelas from the gender perspective and the critical discourse analysis (CDA) method. Among our findings, it stands out that, although there are advances in the way of representing women, the symbolic constructions and discursiveness around the female characters continue to yield to the norms of Christian morality, physical stereotypes or the more traditional roles assigned to men and women.